Ultra‐Thick, Low‐Tortuosity, and Mesoporous Wood Carbon Anode for High‐Performance Sodium‐Ion Batteries. Issue 14 (23rd May 2016) - Shen, Fei; Luo, Wei; Dai, Jiaqi; Yao, Yonggang; Zhu, Mingwei; Hitz, Emily; Tang, Yuefeng; Chen, Yanfeng; Sprenkle, Vincent L.; Li, Xiaolin; Hu, Liangbing
Abstract : Pyrolysis of earth‐abundant wood yields to ultra‐thick, low‐tortuosity, and mesoporous carbon anodes for sodium‐ion batteries. Such a low‐tortuosity and porous structure promotes electrolyte diffusion and provides fast transport channels for Na ions, which enables a high areal capacity.